The Effects of Spatially Targeted Enterprise Initiatives: Evidence from UK LEGI - Henry Overman; Elias Einio (European Regional Science Association (ERSA), 2012)
We investigate the impacts of a significant area-based policy intervention (LEGI) that aimed to increase employment and productivity in 30 disadvantaged areas across England. In order to identify the causal effects of the programme, we use panel data at a fine spatial scale covering years before and after the launch of the program, and exploit several institutional features that determined whether or not an area becomes supported. Using spatial differencing, we find evidence of significant displacement from non-treated to treated areas close to the treatment area boundary. Aside from this displacement, we find little evidence of significant impact on treated areas nor of a net impact of treatment once we take account of this displacement. Spatial differencing combined with a regression discontinuity approach based on eligibility criteria confirm these findings.
Keywords: 330